Changing from a Rules-based to a Principles-based Accounting Logic: A Review - Marta Silva Guerreiro; Lúcia Lima Rodrigues; Russell Craig (Australasian Accounting, Business and Finance Journal, 2014)
We explore influences on unlisted companies when Portugal moved from a code law, rules-based accounting system, to a principles-based accounting system of adapted International Financial Reporting Standards (IFRS). Institutionalisation of the new principles-based system was generally facilitated by a socio-economic and political context that increasingly supported IFRS logic. This helped central actors gain political opportunity, mobilise important allies, and accommodate major protagonists. The preparedness of unlisted companies to adopt the new IFRS-based accounting system voluntarily was explained by their desire to maintain social legitimacy. However, it was affected negatively by the embeddedness of rule-based practices in the ‘old’ prevailing institutional logic.
Keywords: Change; IFRS; institutional; Portugal; principles; rules